Physical activity practice and physical self-concept in students. - Torres Pérez, Amanda; Gavala González, Juan; Fernández García, José Carlos (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to determine the relationship between the physical activity levels and physical self-concept in a sample of adolescents (N = 97) who were studying Physical Activity and Sports-related studies. For this purpose, they were administered the International Physical Activity Questionnaire – short version (IPAQ - SF) and the Physical Self-Concept Questionnaire (CAF). The results allow us to affirm that the students of training cycles related to sport were more physically active than the recommendations suggested by the WHO (91,8% high level of PA). Furthermore, it was found a direct relationship between the practice of physical activity and physical self-concept and its dimensions, except for physical attractiveness (HF: rho = 0,24; p = 0,017 < 0,05; CF: rho = 0,43; p = 0,000 < 0,01; F: rho = 0,35; p = 0,001 < 0,01; AG: rho = 0,28; p = 0,006 < 0,01), and that higher intensity physical activity is related to a better general physical self-concept (diff mean = 4,23; p < 0,01) and greater physical fitness (diff mean = 3,78; p < 0,05) and strength (diff mean = 3,81; p = 0,056). Therefore, physical activity seems to be a positive value for physical self-concept.